Viscosity, Thermal Conductivity and Thermal Diffusion Ratio of the Alkali Metal Vapours. - Fialho, Paulo (1994)
The Subcommittee of Transport Properties of IUP AC started in 1982 a project with the objective of correlating and predicting the transport properties of the alkali metal vapours, in the temperature and pressure zones that are useful to the scientific and industrial uses. In a recent paper [1] the authors suggested a new approach to assess the available experimental data, based in the kinetic theory of gas mixtures, which is a modification of the method developed by Vargaftik and Yargin[2]. In the present communication, we present the surfaces for the viscosity and thermal conductivity, and thermal diffusion ratio which have been developed for lithium, sodium and potassium with average uncertainties of 1%, 0.5% and 0.5%, respectively, for temperature ranges 800-2000 K (lithium) and 700-1500 K (sodium and potassium). . For rubidium and cesium, the available data does not allow a similar development of the corresponding surfaces. It is interesting to note that no clear evidence for the presence of dimers was found for cesium within experimental uncertainty.